Efektivitas Penyaluran Zakat Oleh Lembaga Amil Zakat Terhadap Peningkatan Ekonomi Mustahik Di Kecamatan Medan Timur - Fanisa Hasibuan; Hagi Arfan Prawira; Nurhaliza Azzahra; Yenni Samri Juliati Nasution (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effectiveness of zakat distribution by zakat collection agencies in improving the economic conditions of mustahik in the Medan Timur subdistrict. The study employed a descriptive qualitative approach, using in-depth interviews as the data collection method with eight mustahik recipients of productive zakat assistance and two informants from the zakat management team specifically, a staff member from the economic empowerment program and a zakat distribution coordinator. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the distribution of productive zakat by zakat management institutions has been effective. The forms of assistance provided include business capital, business equipment, business carts, sewing machines, training, and business mentoring. The program’s effectiveness is evident in increased business income, expanded business activities, a growing number of customers, improved ability to meet family needs, and the emergence of savings capacity among the majority of zakat recipients. Furthermore, the zakat distribution process involves several stages—including application submission, field surveys, data verification, eligibility assessment, and periodic monitoring and evaluation ensuring that the assistance provided is well-targeted. Nevertheless, several challenges remain, such as limited funds, fluctuations in raw material prices, business competition, and low levels of business management skills and financial literacy. Based on the research findings, it can be concluded that the distribution of productive zakat by zakat collection agencies in the Medan Timur subdistrict is effective in improving the economic well-being of zakat recipients. Therefore, it is necessary to improve the quality of mentoring, provide entrepreneurship training, and conduct ongoing business monitoring so that the economic self-reliance of zakat recipients can be optimally achieved.